The limits of social science : causal explanation and value relevance - Hammersley, Martyn (Los Angeles : SAGE, 2016)
This work engages with key intellectual challenges facing social science today, at a time when it is under considerable pressure to demonstrate its value. It addresses questions that carry implications for research practice, quantitative or qualitative, by making use of contemporary examples, such as the London riots.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Great Britain